Cover Picture: A Study on Consumption and Characterization of Stabilizer Content of NEPE Propellant via FTIR (Prop., Explos., Pyrotech. 7/2019). Issue 7 (8th July 2019) - Tao, Tao; Sui, Xin; Li, Shipeng; Wang, Ningfei
Abstract : The cover picture shows the change rule of stabilizer content in the aging process of NEPE propellants, and the relationship between stabilizer content of NEPE and the characteristic second derivative absorption band of its infrared spectrum. The propellant samples were placed in the high temperature ageing test chamber, then the stabilizer content and infrared spectrum were tested regularly. On one hand, a stabilizer consumption equation containing stabilizer content, the ageing temperature and time was established by analyzing the data. On the other hand, it was found that the second derivative spectral absorbance of 1598 cm −1 has a high linear correlation to the stabilizer content of NEPE propellant, and an equation, which can be used to calculate the stabilizer content of NEPE with FTIR data, was established. More details are discussed in the article by Tao Tao, Xin Sui, Shipeng Li, and Ningfei Wang on page 889 ff.